Increased Efficiency of the Artificial Bee Colony Algorithm Using the Pheromone Technique - Alaidi, A. H.; Soong Der, C.; Weng Leong, Y. (Engineering, Technology & Applied Science Research, 2022)
Artificial Bee Colony (ABC) is a powerful metaheuristic algorithm inspired by the behavior of a honey bee swarm. ABC suffers from poor exploitation and, in some cases, poor exploration. Ant Colony Optimization (ACO) is another metaheuristic algorithm that uses pheromones as a guide for an ant to find its way. This study used a pheromone technique from ACO on ABC to enhance its exploration and exploitation. The performance of the proposed method was verified through twenty instances from TSPLIB. The results were compared with the original ABC method and showed that the proposed method leverages the performance of ABC.